Growth and Yield Response of BRRI dhan28 to Phosphorous Rates in Batiaghata Upazila of Southwestern Bangladesh (South Asian Journal of Agriculture, 2019)
The experiment was carried out during the period from January to May, 2018 at Professor Purnendu Gain Field Laboratory of Agrotechnology Discipline, Khulna University to evaluate the effect of phosphorous (P) on yield and yield attributes of BRRI dhan28. The experiment was consisted of seven P doses viz. T0 = without phosphorus (P), T1 = 9 kg P ha-1, T2 = 12 kg P ha-1, T3 = 15 kg P ha-1, T4 = 18 kg P ha-1, T5 = 21 kg P ha-1 and T6 = 24 kg P ha-1 as treatments. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Only the grain yield and biological yield showed significant variations due to the effect of different rates of phosphorous. Others growth and yield attributes varied insignificantly. The result of this experiment showed that the highest grain yield (3.82 t ha-1) and biological yield (10.87 t ha-1) was obtained from 21 kg P ha-1 (T5). There was an increasing trend of grain yield with the increase of phosphorous level up to 21 kg P ha-1 and then it declined. From the result of this experiment it could be revealed that 21 kg P ha-1 gives better result regarding grain yield of HYV rice variety BRRI dhan28 at Batiaghta upazila of southwestern Bangladesh.South Asian J. Agric., 7(1&2): 30-33